ANTI-MICROBIAL EVALUATION OF NEW THIAZOLO PYRIMIDINE DERIVATIVES - Ahmed A. Fayed; Samah Ghanem (European Scientific Journal, ESJ, 2013)
Twelve new heterocyclic compounds containing thiazolo pyrimidine moiety were thus synthesized.. Compound 2 was synthesized by reaction of α-amino naphthol 1 with potassium isothiocyanate. Reaction of compound 2 with sodium nitrite and hydrochloric acid afforded the corresponding diazonuim salt 3, which converted to 2-hydrazino thiazolo derivatives 4. Compound 2 carried out to synthesize imidazolo thiazolo derivative 5, 6 and thiazolo pyrimidino derivative 7, 8 and 9 respectively. Compound 4 was carried out to synthesize of compound 10. Compound 10 was carried out to synthesize of triazolo thiazolo and thiadiazolo derivatives 11 and 12 respectively. The structures of all newly synthesized compounds were elucidated by elemental analysis, IR, 1H-NMR and mass spectral data. The assignments of the new products were tested for Anti-microbial activities. Results are suggesting thiazolo pyrimidine derivatives emerge as valuable compounds with great potential to be used as antibacterial and antifungal agents, and as promising candidates for further efficiency evaluation. The detailed synthesis, spectroscopic data and Anti-microbial activities are reported.